If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5-2x+(-8)=-11
We move all terms to the left:
5-2x+(-8)-(-11)=0
We add all the numbers together, and all the variables
-2x+8=0
We move all terms containing x to the left, all other terms to the right
-2x=-8
x=-8/-2
x=+4
| 5/7x-6(-6)=16 | | 2b−2=2 | | -3x-24=-36 | | -1x+8=3x+4 | | 3x^2+5x=-61 | | 15-5y+4-(-3y)=20 | | 3x^2+5x=61 | | x+2(x-1)=5/2 | | 4n-5=-81 | | 5(2-r)=20 | | 3x2+5x+61=0 | | (7-x)/5=-14 | | x/15=15/(x+16) | | 10-9b=-8 | | x/15=15/x+16 | | 1x+2=2x+3 | | 15(2x-3)=-15 | | 5p-2=-67 | | 12x=56/3 | | 0.3(6+m)=0.4(8-m( | | (6)/(x+1)=(1)/(2) | | 15(x+6)=75 | | (6)/(x)+(1)=(1)/(2) | | 4x-1x-8=1x+12+14 | | 1-2x+5-9=0 | | 6x+2x+15=3x+3x+37 | | 13=10=p/2 | | 20x-6=114 | | 2-7m=107 | | n/7+7=5 | | -5(x+6)-5=-15 | | 41=+6+5u |